Analysis of Slope Stability Using Geotextile with The Limit Equilibrium Method in Gunung Sari, Batu - Sholeh, Moch.; Cupasindy, Dyah Ayu Rahmawati; Anggraini, Novita; Asema, Fuji; Susilo, Helik (CIVED, 2024)
Gunung Sari Village, Batu City is a hilly mountainous area. Where the elevation contour of the land is at an altitude of ± 800 meters above sea level. Because of its hilly location, there are many steep slopes around the location. These slopes have the potential to experience landslides, considering that the rainfall in these locations is very high. Potential slopes with such conditions are suspected to have a safety factor (SF) < 1. For this reason, researchers are interested in analyzing the slopes on these slopes using the limit equilibrium method. In this study the method that will be used is to analyze the factor of safety in the existing conditions and the factor of safety after the slope is given geotextile reinforcement which will be modeled with the Geoslope/W 2012 application. The results of the safety factor analysis of existing conditions at cross 1 using the Geo Slope/W 2012 Program, the Bishop method, is 0.851, while for the Morgenstern method it is 0.961. Both methods show a safety factor value of less than 1 (F<1), which means the slope is unstable and has a high potential for landslides. The value of the safety factor with geotextile reinforcement for both methods has increased, making the slope more stable (F>1). The safety factor value for cross 1 of the Bishop method is 1.698 while for the Morgenstern method it is 1.702.